Nauczanie śpiewu indywidualnego w szkole muzycznej I stopnia – repertuar, zalety, wskazówki metodyczne - Wójcik-Ilnytska, Paulina (Chowanna, 2024)
This article deals with the problem of individual vocal training of children and adolescents in first- degree music school. The author considers the choice of repertoire to be of crucial importance in the learning of singing at this stage of education, as it determines the development of a student’s interest in singing, his/her progress and often the choice of his/her further artistic path. The selection of repertoire for children should take into account many issues, including the maturity of the child’s vocal tract and its emotional and musical development, which determines the achievement of correct emission and musical interpretation. It is also important to get children interested in performing the songs of Polish composers; the author of the article presented repertoire items that can be used in vocal work with children under the age of 16. In discussing the issue of individual singing lessons in first degree music schools, the issues of voice emission and interpretation of vocal works by young performers, as well as the impact of singing lessons on the development of musical abilities of children and adolescents are also included.